Types of the Fiber Glass-Mat on Fatigue Characteristic of Composite Materials at Constant Fiber Volume Fraction: Experimental Determination - Al-Alkawi, Hussain J.; Al-Fattal, Dhafir S.; Ali, Abdul-Jabar H. (Al-Khwarizmi Engineering Journal, 2012)
The aim of this work is to study the influence of the type of fiber glass –mat on fatigue behavior of composite material which is manufactured from polyester and E-glass (woven roving, chopped strand mat (CSM)) as a laminate with a constant fiber volume fraction (VF) of 33%. The results showed that the laminates reinforced with E-glass (woven roving) [0/90, ±45.0/90] and [0/90, CSM, 0/90] have lower fatigue strength than the laminates reinforced with E-glass [0/90]3,[CSM]3 and [CSM, 0/90, CSM]  although they had different tensile strength; the best laminate was [0/90]3 .